Female urinary incontinence: a systematic overview and non-surgical treatment - Ngarambe, Cosette; Peng, Dan-hong (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Urinary Incontinence was acknowledged in 1998 by World Health Organization as a disease, to raise the awareness of the condition. Literature suggests that 50% of the incontinent women would be less than 50 years of age. Despite the great evolution in the area of gynecology, incontinence remains a real problem for number of women around the world. In some area the embarrassing nature of urinary incontinence has lead women to hide the existence of syndromes. Most of the women will seek health care at a late stage, when there is little or nothing to do. Alternative opportunity of surgery reveal to be a costly choice as popular believes that urinary incontinence is a fatality to all women. Little is known or rather little is provided to women in order to understand the process which causes urinary incontinence, whereas to the shame inflicted to them. This review paper aims to give a systematic overview of female urinary incontinence, and to a certain extent to present its non-surgical approach.